PENERAPAN STRATEGI DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI RUPA DI KELAS VII 6 SMP NEGERI 26 PADANG - Drs. Yusron Wikarya, M.Pd., SITI SYAWALINA, Dra. Zubaidah, M.Pd., (Jurusan Seni Rupa FBS UNP Padang, 2017)
The purposes of this research is to increase Fine Art the study result of student by implemented strategy discovery learning on student class VII 6 state SMP 26 of Padang. The kind of this research is research of class action (PTK) by a research subject student on class VII 6 state SMP 26 Padang a mount 36 people. Data collecting tool at this research it is student activity format, teacher format activity and the result study of evaluation sheet. The result of the research to show the increase of student percentage activity at cycle I is 59,07%, increase be 84.6% at cycle II.. Meanwhile the result thoroughness studies of student at cycle I is 77,77% and increase at cycle II by result thoroughness studies of student is 100%.Kata kunci : Strategi Discovery Learning, Hasil Belajar, Seni Rupa